Perbandingan Kualitas Buku Teks Bahasa Arab Tingkat Madrasah Tsanawiyah - Ma’arif, M Syamsul; M. Syamsul Ma’arif (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Choosing good Arabic textbooks determines the quality of Arabic learning in the classroom. This paper aims to identify and compare the quality of the Arabic language textbooks at Islamic junior high school levels seen from the aspect of content, presentation, language, and graphic. The object of research is the book of D Hidayat, Maman Abdul Djalil, and A. Syaekhuddin and Hasan Saefullah. The results showed that all three of the Arabic language textbooks have advantages and disadvantages. In general, the Arabic textbook work of A. Syaekhuddin and Hasan Saefullah is better than the other two books.